EVALUASI KEMANDIRIAN DAERAH DALAM PENGELOLAAN KEUANGAN DAERAH (STUDI PADA PEMERINTAH KOTA KENDARI) - Rimporok, Christian; Haerani, Haerani (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTACKThis research aims to determine the level of financial independence to the reception area of the original income of Kendari City by comparing the transfer of funds from the central government. Data was collected by interviews and documentation. The analytical method used is ratio analysis method. Equipment used in the study is the Regional Independence RatioThe results of this study showed that the ratio of local government Kendari City already does not depend kepaada transfer funds from the province during the period 2012 to 2013. It can be concluded that the independence of the regional government of Kendari in meeting the funding requirements to perform the duties of governance, development, and social service to the community has been very high and even increased year by year, from 111% in 2012 to 112% in 2013. This means that the governments dependence on equalization fund Kendari City center is already very low.Â Keywords: Independence Regional, Local Revenue Receipts, and Fund Balance/Funds Transfer